How long can you keep working with benign multiple sclerosis?. Issue 1 (27th August 2010) - Glad, Solveig B; Nyland, Harald; Aarseth, Jan Harald; Riise, Trond; Myhr, Kjell-Morten
Abstract : Objective: To study employment in benign multiple sclerosis (MS), the frequency of employment was analysed and the effect of early clinical and demographic factors on time to disability pension was evaluated in a population based MS cohort. The frequency of depression, cognitive function, fatigue and pain between benign and non-benign MS patients was compared, and their impact on employment in benign MS was studied. Methods: All 188 patients alive, including 60 benign patients with onset of MS during 1976–1986 in Hordaland County, Western Norway, were interviewed and clinically examined in 2003. The Expanded Disability Status Scale (EDSS), depression (Beck Depression Inventory), cognitive function, fatigue, pain, year of disability pension, employment and type of occupation were registered. Benign MS was defined as an EDSS score ≤3.0 at least 10 years after disease onset. Results: After a mean disease duration of 22.2 years, 32.4% of the cohort were still employed. A relapsing–remitting course, higher educational level and light physical work were significantly associated with longer time to disability pension in the general MS population. Thirty-nine (65.0%) benign MS patients were employed, independent of light or heavy physical work. Mild depressive symptoms were markedly associated with not being employed in benign MS (OR=7.3). Conclusions: A relapsing–remitting course, higher educational level and light physical work significantly predicted longer time to disability pension in the total MS population. Among the benign MS patients, depressive symptoms, although mild, were strongly associated with not being employed.